Pinacoteca Psiquiátrica en España, 1917-1990 - Ana Hernández Merino (Arteterapia)
The exhibition Psychiatric Art gallery in Spain 1917-1990 presented in the University of Valencia in October, 2009 gathers more than three hundred artistic works of mental patients from particular and institutional collections who in the main have remained imprisoned in the psychiatric area and out of the cultural sphere. The psychiatrists’ interest like Gonzalo R. Lafora, Joan Obiols or Ramon Sarró have made possible the conservation of the works or of institutions as Ciempozuelos’s Hospital, that of Toen or Artists’ Plásticos Línea Parallel association between others. The look of the patients from his experience of the madness proves to be crossed by instants of beauty and suffering. They are capable of affecting with worrying, strange images and in turn familiar that they point at the sinister thing as something foreign and simultaneously daily, attractively and disturbing.